A survey on Biostatisticians Serving in the Italian Ethics Committees (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Italian ethics committees (ECs) have the responsibility for evaluating and monitoring clinical research.Methods. An electronic survey targeted to the biostatisticians operating in the 95 ECs in Italy, was launched in November 2016. Several aspects were explored such as education, job title, training in biostatistics and experience in the evaluation of protocols within the EC.Results. Seventy case report forms were returned (74%), and the response rate was highest for ECs located in the South (78%) and lowest in the North (51%). The biostatisticians in the respondent ECs were prevalently male, aged 50-60 years, with postgraduate education in medical specialties and statistics. The annual workload varied depending on the type of institution and geographical area, with an annual median number of protocols examined ranging from 80 in hospital ECs to 198 in university hospital ECs, and from 80 to 108, in the South and the Centre, respectively. Of these, 40% were observational study protocols. The EC biostatisticians proposed to reject 5% of protocols and to suspend with the request of clarification or amendments 10%. Only 61% and 79% of these opinions, respectively, were regarded as binding by the other EC members.Conclusion. The biostatistician will not be able to play a significant role in the EC as long as the required skill-set remains vague and his/her opinion on a protocol is underrated.